2002
DOI: 10.1021/jp013569a
|View full text |Cite
|
Sign up to set email alerts
|

An AC Impedance Spectroscopic Study of LixCoO2 at Different Temperatures

Abstract: An AC impedance spectroscopic study of the Li x CoO 2 electrode in the temperature range of 0-30 °C is presented. The results are interpreted on the basis of an equivalent circuit that includes elements related to the electronic and ionic transport in addition to the charge transfer process. The evolution of the impedance spectra with the temperature shows that a thermally activated insulator to metal transition occurs at the beginning of the deintercalation process. At intermediate intercalation degrees, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
72
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 32 publications
13
72
1
Order By: Relevance
“…These values are in agreement with previously reported ones in literature (0.2-0.45 eV) associated to the electronic and ionic transport phenomena in LCO. 49,[54][55][56][57][58][59] Notice that this value is considerably lower than for LiAlO 2 , which lays above 0.7 eV in the temperature range C, 60 discarding the formation of this compound in a signicant amount in agreement with Han et al 29 and XPS (Fig. 3e).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…These values are in agreement with previously reported ones in literature (0.2-0.45 eV) associated to the electronic and ionic transport phenomena in LCO. 49,[54][55][56][57][58][59] Notice that this value is considerably lower than for LiAlO 2 , which lays above 0.7 eV in the temperature range C, 60 discarding the formation of this compound in a signicant amount in agreement with Han et al 29 and XPS (Fig. 3e).…”
supporting
confidence: 76%
“…But it is worth mentioning that the fully lithiated LiCoO 2 is at least 4 orders of magnitude less electronically conductive in the majority of published literature. [49][50][51] Moreover, the preferred orientation and lm porosity may also inuence the measured conductivity. 52,53 According to our previous results, our sputtered LCO thin presents (003) preferred orientation and highly porous morphology.…”
mentioning
confidence: 99%
“…In the past decades, EIS has been extensively used in the analysis of lithium battery systems, especially to predict the behavior of batteries, and to determine the factors limiting the performance of an electrode including its conductivity [75,126], charge-transfer properties [11,103,[117][118][119], properties of the passivating layer, etc. Numerous recent studies have been published on various aspects of the insertion electrodes used in lithium-ion batteries for the attempt to understand the origin of the observed capacity loss during extended cell cycling or storage [1,30,37,52,66,78,97].…”
Section: Introductionmentioning
confidence: 99%
“…So the electrical conductivity of the component materials is one of the most important issues in connection with the intercalation electrode reaction. Nobili and co-workers [25,61,[72][73][74][75] suggested that the Nyquist plots of LiCoO 2 in the delithiated state should involve a third semicircle relating to the electronic propetries of the material, however, the three suggested semicircles could not be observed in their experimental results. In our previous work [126], as illustrated in Figure 2-5, at intermediate degrees of the first delithiation process in spinel LiMn 2 O 4 electrode, three semicircles are observed in the Nyquist diagram, and it was demonstrated that the semicircle in the middle to high frequency range (MHFS) should be attributed to the electronic properties of the material.…”
mentioning
confidence: 99%
“…Adsorption and desolvation should, therefore, correspond to the main contribution to the total cell impedance and hence to the semicircle conventionally attributed to charge transfer. This concept is hardly new as it has been applied to the lithium intercalation in the case of different lithium intercalating compounds [26][27][28]. The decreased resistance associated with the middle-frequency semicircle at- tributed to the 'charge transfer process', and hence the improved kinetics caused by the presence of the metal at the surface for layer thickness up to 250 Å, can be explained assuming a catalytic effect of the metal towards the desolvation reaction.…”
Section: Introductionmentioning
confidence: 99%